Group guidance with photovoice technique to increase empathy of student - Warsongko, Denok Setiawati; Miranda, Sarah Kurnia; Ghozali, Muhamad Afifuddin (Journal of Professional Teacher Education, 2024)
This research aims to measure the increase in student empathy after implementing group guidance using the photovoice technique. The type of research is quasi-experimental without a control group used in this research. The research subjects were 10 students with high, medium, and low empathy scores randomly determined as the research sample. The implementation procedure was carried out in six sessions using a plan designed collaboratively between group guidance and photovoice techniques. This research shows differences in scores before and after receiving treatment. The Wilcoxon test was carried out to analyze the data with an assumption sig (2-tailed) result of 0.005, which showed that the alternative hypothesis that applying photovoice technique group guidance could increase Surabaya students' empathy was accepted. The conclusion that can be drawn from this research is that group guidance using the photovoice technique can improve empathy skills. The findings imply that integrating photovoice techniques into group guidance programs offers an effective strategy to foster empathy in educational settings. This approach provides a participatory and reflective platform for students, enhancing their emotional awareness and social understanding. Such interventions can be widely applied to support character development and social-emotional learning initiatives in schools.